Pemanfaatan Aplikasi Video Conference Google Meet Dalam Pembelajaran Bahasa Inggris Secara Daring Pada Siswa SD Negeri Ciledug Barat, Pamulang, Tangerang Selatan - Resti Isnaeni; Pari Purnaningsih (CV. Multi Kreasi Media, 2022)
In education, students’ English skill are indispensable in learning process. The teacher as facilitator will provide the best teaching and learning process for students. English is a subject that develops communication skill both orally and writing, understands and expresses some information. This subject is no longer that limited grammar but it can also develop students’ skill in communicating. For this reason, creative methods are needed that can make students more active and interesting in learning English. However, due to the covid-19 pandemic, English learning activities are now offline. Even though learning is done online, teachers must be able to provide knowledge in an interesting and creative way. One of the methods used in online learning is by using the Google Meet Video Conference application, where teachers and students can still meet face to face, even though virtually. The purpose of this study was to (1) determine the online English learning plan using the Google Meet Video Conference application at SD Negeri Ciledug Barat, Pamulang, South Tangerang. (2) Knowing the implementation of online English learning by using the Google Meet Video Conference application at SD Negeri Ciledug Barat, Pamulang, South Tangerang. (3) Determine the evaluation of online English learning by using the Google Meet Video Conference application at SD Negeri Ciledug Barat, Pamulang, South Tangerang. (4) Knowing the obstacles faced and how to overcome them in learning English online by using the Google Meet Video Conference application at SD Negeri Ciledug Barat, Pamulang, South Tangerang. This research begins with conducting field studies, identifying and formulating problems, then proceeding with determining goals and collecting data and processing data. In the end, this research will produce scientific papers that are presented in seminars on the use of the Google Meet video conference application in online English learning for students at SD Negeri Ciledug Barat, Pamulang, South Tangerang.